Reverse logistics network design of e-waste management under the triple bottom line approach. (1st November 2020) - Safdar, Nimra; Khalid, Rabia; Ahmed, Waqas; Imran, Muhammad
Abstract: Enhancing social and economic effects along with reducing environmental effect has gained significant consideration in reverse logistics network design. Electronic waste management raises serious concerns due to its increasing quantity and hazardous nature in global business. The developed model is a multi-objective reverse logistics network for electronic waste management, and the concept of the triple bottom line approach has been considered in the proposed study. The suggested study makes a trade-off between conflicting objectives. The research considers first customers, collection centers, distribution centers, second customers, and reprocessing units consisting of return evaluation centers, recycling centers and refurbishing centers. The carbon cap-and-trade policy has also been incorporated into the model. The objectives of the formulated model are to maximize the profit and minimize the carbon emissions as well as maximizing the job opportunities in a reverse logistics network. To deal with the uncertainty, neutrosophic optimization has been applied to avoid unrealistic modeling. A related numerical example has been performed and the results show that the transportation cost contributes to the major fraction of the total cost. The reprocessing at the return evaluation and recycling centers are the main source of carbon emissions. Sensitivity analysis has also been conducted to assess the application of the proposed model. It shows that a drastic increase of 42.6% occurs in the profit value when the per-unit carbon trading price is increased by 40% and vice-versa. Also, a variation is seen in the parameters like carbon emissions at recycling center with a change in total emissions value and the average number of units processed by one worker at return evaluation center with a variation in the number of job creation value. Highlights: Sustainable reverse logistics management for electronic waste is considered. Social, economic and environmental aspects are integrated simultaneously. Creation of new job opportunities in processing units and transportation sector. Application of carbon cap-and-trade policy to minimize emissions. Neutrosophic optimization approach is applied to improve the network.